Analysis of Consumer Attitude, Value, Customer Satisfaction on Interest to Buy in Top Supermarkets - Rike Selviasari; Diana Ambarwati (STIE Amkop Makassar, 2022)
The purpose of this study is to look at how sacrifice affects value, how consumer attitudes affect value, how consumer attitudes affect consumer satisfaction, how consumer attitudes affect buying interest, how value affects consumer satisfaction, how value affects buying interest, and how consumer satisfaction affects buying interest. This study is a hypothesis-testing study using the survey method, as stated in the objectives. The study's target population is 100 people, which includes all Kediri Top Supermarket customers. Purposive sampling is the technique utilized. Pretest, validity and reliability, estimation, and structural model testing were the test instruments employed in this study. It employed Structural Equation Modeling to test it (SEM). The study's findings revealed that: (1) Sacrifice had a significant effect on the value. (2) Consumer attitudes have a significant effect on the value. (3) Consumer attitudes have a significant effect on consumer buying interest. (4) The value has a significant effect on consumer satisfaction. (5) Consumer satisfaction has a significant effect on consumer buying interest.